So long, insecurity [compact disc, unabridged] : you've been a bad friend to us - Moore, Beth, 1957- (Tyndale Audio, 2010)
Beth Moore speaks truth into the lives of readers, showing them how to deal with their innermost fears, rediscover their God-given dignity, and develop a whole new stronger sense of self. Women of all ages and backgrounds will identify with this message of security and discover truths that will free them emotionally and spiritually and lead them to a better life as they walk with God.